DNA Extraction of Cynopterus brachyotis of Labuhan Ratu VII Based on Column Method in Supporting its Molecular Species Confirmation - Annisa Lidya Maharani; Elly Lestari Rustiati; Priyambodo Priyambodo; Eko Agus Srihanto; Enny Saswiyanti; Dian Neli Pratiwi; Alvin Wiwiet Susanto (Ann Publisher, 2025)
Background. Bats (Chiroptera) are true flying mammals and nocturnal. Ecologically, bats play important roles as pollinators, seed dispersers, guano producers, biocontrol, and hosts a range of viruses. Cynopterus brachyotis belongs to fruit-eating bats and is considered morphologically cryptic with C. sphinx. Aims. To support morphological identification, molecular species confirmation needed to be conducted. DNA extraction, as an initial step, plays a crucial role in molecular analysis. Methods. The quality and quantity of extracted DNA determine the success rate of sequencing for species confirmation in bats. In this study, oropharyngeal samples were used. Result. The research procedures included bat capture and DNA oropharyngeal swab sample collection, sample preparation, DNA extraction using a silica column-based commercial kit, DNA concentration measurement using a Qubit assay, and electrophoresis. Conclusion. The Qubit assay showed DNA concentrations of >1 ng/µL, while electrophoresis did not reveal bright DNA bands.